Abordagem para identificação, análise e caracterização dos estágios de desenvolvimento dos clusters: um estudo em regiões metropolitanas - Manzini, Reinaldo Belickas (2013)
The study of the cluster phenomena, during the last 30 years, under numerous qualifications, has attracted increasing attention from both the academia and those responsible for the development of public policy. However, their development cycle is still an unexplored aspect. The necessity to investigate and understand the cluster life cycle is highlighted by several authors. From the public policy perspective, the importance of identifying the cluster life cycle, as well as each of its stages, is the assertiveness that they provide. The thesis is presented in the form of three papers. The first seeks to determine the nature and dimensions of the notion of cluster exploring the theoretical and conceptual knowledge of three areas in which the concept is most commonly employed: economic geography, strategic management and operations management. Among other findings, the results provide a classification of research topics around the concept and theoretical and conceptual lines that sustain them. The second deals with the question of how clusters are identified. Leaving some limitations from regional economy statistics, especially Locational Quotient (LQ), the author proposes a joint application of these statistics with those presented by the Exploratory Spatial Data Analysis (ESDA). The results show the complementarity of approaches, once the constraints from the former can be solved by the latter, but more importantly, they reveal the value provided by ESDA about regional dynamics. Finally, the third and final article proposes an instrument to evaluate the cluster life cycle involving 6 dimensions and 11 factors for evaluation. From the potential clusters identified in the second article, the instrument is applied on three of them. The result is a simple, practical, conceptually consistent and lowcost implementation life cycle evaluation approach.